Perancangan Aplikasi Pemesanan Ayam Potong Pada Kandang Ayam Broiler Berbasis Android Di Kampung Perlabian - Apriana Putri Hasibuan (Universitas Labuhanbatu, 2022)
The chicken cage (broiler) owned by Indra Satria Hasibuan is one of the chicken breeding business (broiler) which has a capacity of 5,000 chickens and the farm has cooperated and has signed a contract with PT. Charoen Pokphand Indonesia (CPIN). This chicken cage (broiler) also has several agents that have been registered or can be said to have worked with the owner of the cage (admin). . However, the broiler chicken ordering process and agent registration is still done manually by recording each data agent who has cooperated with the owner of the cage (admin) and recording the order data that has been sold in a book so it is less efficient. To overcome this we need an application that can facilitate the admin in registering a new agent and view order data that has been inputted or added by the agent, and allows the agent to order chicken (broiler) via a smartphone or can be said not to come directly or to the location. Broiler chicken ordering application is designed and designed using UML (Unified Modeling Language) modeling. Broiler chicken ordering application was built using Eclipse and Mysql as a database for data storage. The result of this application design is an android-based broiler chicken ordering application that can be used to record agents and order broilers via a smartphone.